Transitory masculinities in the context of being sick with prostate cancer - Jeferson Santos Araújo; Vander Monteiro da Conceição; Marcia Maria Fontão Zago (Universidade de São Paulo, 2019)
Objective: to interpret the meanings attributed by men with prostate cancer to the experience regarding their bodies and masculinities during illness. Method: ethnographic research with 17 men, guided by the narrative method and theoretical framework of medical anthropology and masculinities. The information was collected through recorded interviews, direct observation and field diary records, which were analyzed by inductive thematic analysis. Results: men undergo body and identity transformations when they get sick with prostate cancer, transiting through multiple masculinities, resigning their actions, and occupying subordinate positions in relation to other healthy bodies, which are marginalized in their social relationships and allied with regard to establishing their affective relationships. Conclusion: this evidence enhances and deepens the knowledge disclosed in the literature and contributes to the strengthening of nursing care actions when dealing with the sick.